1,8-cineole as an antimicrobial and antibiofilm agent against multidrug resistant Klebsiella pneumoniae - Vázquez, Nicolás Martín (2021)
Klebsiella pneumoniae is a common cause of antimicrobial-resistant opportunistic infections in hospitalized patients, including urinary tract infections. The emergence of multidrug-resistant (MDR) strains producing extended-spectrum β-lactamases (ESBL) and/or carbapenemases, in combination with the capacity to produce biofilm has created additional problems in providing adequate antibiotic treatment of urinary tract infections. Biofilms are complex bacterial communities adhered to biotic or abiotic surfaces that are surrounded by an extracellular matrix composed of exopolysaccharides, proteins and nucleic acids that give them differential phenotypic properties associated with greater resistance to antibiotics. 1,8-cineole, one of the main components of Rosmarinus officinalis volatile oil, has shown antimicrobial activity against non-MDR Gram negative bacteria (including K. pneumoniae) during planktonic growth. Here, we evaluated the antimicrobial and antibiofilm activity of 1,8-cineole against planktonic and pre-formed mature biofilms of non-MDR and MDR ESBL-producing K. pneumoniae clinical strains isolated from urinary tract infections. Killing curves were performed in planktonic cultures by adding 1% (v/v) 1,8-cineole for 5-180 min and counting viable cells (cfu/ml). Results showed variable decrease of K. pneumoniae viability (ranging from 0.5 to 4 log reduction) after phytochemical treatment, not related to their antibiotic resistance profile. Regarding biofilms, all tested strains formed robust biomass after 48 h, as determined by crystal violet staining (Abs 595nm > 1). One-hour treatment with 1% (v/v) 1,8-cineole partially disrupted biofilm biomasses (34 to 62% reduction in crystal violet staining). Additionally, a variable decrease in cell viability (between 0,5 and 4 log reduction of ufc/cm2 ) was observed by viable cell counting, regardless if they were or not MDR. Two MDR ESBL-producing K. pneumoniae strains, presenting different susceptibility to 1,8-cineole, were chosen to study their extracellular matrix in biofilms by confocal laser scanning microscopy after calcofluor white staining. Noteworthy, differences in the extracellular matrix structure were observed between strains, that could account for differences in 1,8-cineole susceptibility. Altogether, our results show that some antibiotic-sensitive and MDR ESBL-producing K. pneumoniae isolates were sensitive to 1,8-cineole exposure and support the efficacy of 1,8-cineole as a potential antimicrobial agent for the treatment of planktonic and biofilm-associated infections caused by MDR K. pneumoniae.